2004
DOI: 10.1016/j.ccr.2004.09.032
|View full text |Cite
|
Sign up to set email alerts
|

An autocrine mechanism for constitutive Wnt pathway activation in human cancer cells

Abstract: Autocrine Wnt signaling in the mouse mammary tumor virus model was the first identified mechanism of canonical pathway activation in cancer. In search of this transformation mechanism in human cancer cells, we identified breast and ovarian tumor lines with upregulation of the uncomplexed transcriptionally active form of beta-catenin without mutations afflicting downstream components. Extracellular Wnt antagonists FRP1 and DKK1 caused a dramatic downregulation of beta-catenin levels in these tumor cells associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
298
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(319 citation statements)
references
References 73 publications
14
298
2
3
Order By: Relevance
“…In HCT116 cells, transient expression of V3Nter, SFRP-1 or SFRP-5 induces cell death (Suzuki et al, 2004;Quelard et al, 2008). Consistently, attempts to obtain clones by limiting dilution were unsuccessful, suggesting a negative selection pressure, as shown for SFRP-1 in breast cancer cells (Bafico et al, 2004). However, after seeding three cells per well, several antibiotic-resistant cell populations expressing the relevant epitopes (Supplementary Figure 1a) were expanded.…”
Section: Hct116 Colorectal Cancer Cells Stably Expressing V3ntermentioning
confidence: 65%
See 2 more Smart Citations
“…In HCT116 cells, transient expression of V3Nter, SFRP-1 or SFRP-5 induces cell death (Suzuki et al, 2004;Quelard et al, 2008). Consistently, attempts to obtain clones by limiting dilution were unsuccessful, suggesting a negative selection pressure, as shown for SFRP-1 in breast cancer cells (Bafico et al, 2004). However, after seeding three cells per well, several antibiotic-resistant cell populations expressing the relevant epitopes (Supplementary Figure 1a) were expanded.…”
Section: Hct116 Colorectal Cancer Cells Stably Expressing V3ntermentioning
confidence: 65%
“…Enhanced autocrine Wnt signaling (Bafico et al, 2004) and epigenetic silencing of genes encoding endogenous extracellular Wnt inhibitors (Suzuki et al, 2004) provide a positive selection advantage to cells carrying b-catenin pathway mutations (Barker and Clevers, 2006;Polakis, 2007;MacDonald et al, 2009). In this setting, frizzled receptor activation and enhanced Wnt expression drive positive cancer cell selection (Vider et al, 1996; Smith et al, An SFRP-like frizzled motif blocks tumor growth E Lavergne et al 1999; Dimitriadis et al, 2001;Holcombe et al, 2002;Ueno et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that overexpression of DKK-1 leads to activation of apoptosis after treatment with chemotherapeutic agents or UV. Sensitization to apoptosis was demonstrated in glioma cells [13], Hela cells [2], breast carcinoma cells [11], mesothelioma cells [12]. Activation of apoptosis in DKK-1 expressing cells was suggested is due to increased JNK activity.…”
Section: Discussionmentioning
confidence: 94%
“…[8,10]. Overexpression of DKK-1 resulted in activation of apoptosis in vitro following treatment with different chemotherapeutic agents [11][12][13] and UV irradiation [2]. However it is not known if DKK-1 can activate apoptosis in tumor xenografts in vivo.…”
Section: Introductionmentioning
confidence: 99%